Improving Factors of Divorce Rate in Sabang City - Hendra Surya; Sulaiman Sulaiman; Muzakir Muzakir; Ema Syithah; Baharuddin Baharuddin; Ainon Mardhiah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
The purpose of this study was to look at the factor of increasing divorce rates in the city of Sabang. This research integrates library research and field research using a qualitative approach. This study uses. descriptive method of analysis The highest results of the study showed that the factor of increasing divorce in Sabang City was caused by; first, continuous disputes and disputes amounted to 80 cases, secondly, leaving one party numbered 38 cases, third, economic (family needs not met) as many as 9 cases, fourth, domestic violence in 5 cases, and fifth, sentenced to imprisonment ( involved in the use of narcotics) totaling 4 cases, the data is the data of the last three years. Whereas prevention efforts to avoid divorce are carried out by conducting marriage counseling conducted by the Office of Religious Affairs in the Sabang City area, at least one week before the implementation of the marriage contract, this guidance activity is mandatory for couples to marry, besides the Shari'ah Court of Sabang also conducted mediation with every party who filed a divorce or divorce divorce, out of the 63 cases of mediation cases that entered, only 5 cases of mediation were successfully mediated in the last three years and if the mediation attempt was unsuccessful a register was held to proceed to the trial stage.